PERUBAHAN BENTUK BADAN HUKUM USAHA MILIK DAERAH BERDASARKAN PERATURAN PEMERINTAH NO. 54 TAHUN 2017 DALAM UPAYA PENINGKATAN PENDAPATAN ASLI DAERAH - Ibnu Sam Widodo (Yurispruden: Jurnal Fakultas Hukum Universitas Islam Malang, 2021)
The business entity regulated in Law No. 23 of 2014 which is then technically regulated in Government Regulation No. 54 of 2017 concerning Regional Owned Enterprises in which requires two forms of BUMD, namely regional companies or in short with Perseroda and the second form is Regional Public Company. In many areas there are many forms of business entities that are still in the form of Regional Companies, as a consequence of the enactment of Law No. 32 of 2004 on Local Government and Government Regulation No. 54 of 2017 on Regional Owned Enterprises, each form of Regional Company must be changed to a Regional Company or Regional Public Company. In this journal, the author will explore the procedures for the change from a Regional Company to a Regional Public Company based on Normative Juridical research methods using a statutory approach and literature studies with various literature books, journals, and articles related to the theme that the author adopted. The purpose of the authors to convey from the results of this study is how the influence of changes in the form of regional-owned enterprises in increasing the original income of the region so that the region.